تفسير الآيات الكونية بين رأي المفسرين وعلماء الكونيات - خليل, نجاة; نعيمة, بوذينة; غيلاني, وسيلة (جامعة الوادي university of eloued, 2014)
This project addresses the theme of the interpretation of the cosmic verses between the points of views of the commentators and the cosmic scientists. Where it displays number of the modern and traditional commentators views and the cosmic scientists in studying and explaining some cosmic phenomena. The study concluded, the match between all these views and this what proves that the Holly Quranis the miracle of the prophet Mohammed (PBUH) of all time. So what he brings are facts of the universe from Allah the Almighty and not from himself and what makes him a reason for converting non- Muslims and faith in the hearts of the believers.